MANAGEMENT OF TOURISM FACILITIES AT SEPAHAT BEACH, BANDAR LAKSAMANA DISTRICT, BENGKALIS REGENCY - Arindi "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Sepahat Beach has beautiful natural beauty with a wide expanse of sand located at Jl Jenderal Sudirman RT/RW 02/01 Sepahat Village, Bandar Laksamana District, Bengkalis Regency which has a very strategic location because it faces the Malacca Straits, Malaysia. This study aims to determine the condition of the facilities, the management of facilities and the obstacles experienced in managing tourism facilities on Sepahat Beach, Bandar Laksamana District, Bengkalis Regency. The design of this research is qualitative with descriptive method. The subjects of this study were the government of Sepahat Village and Bumdes of Sepahat Village, with additional informants from visitors to Sepahat Beach. Data collection techniques used are observation, in-depth interviews, and communication studies. The results of this study indicate that Sepahat Beach has facilities consisting of main facilities, namely: gazebo and café, supporting facilities namely: toilets/bathrooms, gazebos, and parking lots, while supporting facilities are: tourism facilities and infrastructure. Sepahat Beach is managed directly by Bumdes using several stages, namely the stages starting from planning. (Planning), Organizing (Actualing) and Supervision (Controlling). The obstacles to the management of existing facilities at Sepahat Beach consist of various aspects both internally and externally, starting from the government which still pays little attention to the Sepahat Beach tourist attraction, then incompetent human resources, especially in the field of tourism, to the lack of public awareness of surrounding environment. Keywords: Sepahat Beach, Management, Facilities